The dinner [compact disc, unabridged] : a novel - Koch, Herman, 1953- (AudioGO, 2012)
On a summer night, two couples meet for dinner at a trendy Amsterdam restaurant. What starts off as friendly conversation quickly changes. Both couples have teenage sons, and those two boys are linked together through a tragic act. Soon, both sets of parents reveal just what they are willing to do to protect their children.